The Bookmark Procedure for Setting Cut-Scores and Finalizing Performance Standards: Strengths and Weaknesses - Lin, Jie (Alberta Journal of Educational Research, 2006)
The Bookmark standard-setting procedure was developed to address the perceived problems with the most popular method for setting cut-scores: the Angoff procedure (Angoff, 1971). The purposes of this article are to review the Bookmark procedure and evaluate it in terms of Berk’s (1986) criteria for evaluating cut-score setting methods. The strengths and weaknesses of the Bookmark are critically examined and discussed. In general, the strengths of the Bookmark method are that it (a) accommodates constructed-response as well as selected-response test items; (b) efficiently accommodates multiple cut-scores and multiple test forms; and (c) reduces cognitive complexity for panelists. Despite unresolved issues like the choice and understanding of the response probability, the Bookmark method remains a promising procedure for setting cut-scores and finalizing performance standards.